2015
DOI: 10.1007/s12199-015-0448-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cerebral blood flow in patients with multiple chemical sensitivity using near-infrared spectroscopy—recovery after olfactory stimulation: a case–control study

Abstract: Objectives Multiple chemical sensitivity (MCS) is a chronic acquired disorder characterized by non-specific symptoms in multiple organ systems associated with exposure to odorous chemicals. We previously observed significant activations in the prefrontal cortex (PFC) during olfactory stimulation using several different odorants in patients with MCS by near-infrared spectroscopy (NIRS) imaging. We also observed that the patients with MCS did not adequately distinguish non-odorant in the late stage of the repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 49 publications
(65 reference statements)
4
21
0
Order By: Relevance
“…This approach is based on the assumption that changes in flow are proportional to changes in velocity only if the diameter of the middle cerebral artery remains constant. Also, the blood flow velocity in the middle cerebral artery can reflect global CBF rather than local CBF [22,23]. On the other hand, a previous study reported that the diameter of the middle cerebral artery can change over a wide range of ETCO 2 (approximately 23-46 Torr) [24].…”
Section: Discussionmentioning
confidence: 99%
“…This approach is based on the assumption that changes in flow are proportional to changes in velocity only if the diameter of the middle cerebral artery remains constant. Also, the blood flow velocity in the middle cerebral artery can reflect global CBF rather than local CBF [22,23]. On the other hand, a previous study reported that the diameter of the middle cerebral artery can change over a wide range of ETCO 2 (approximately 23-46 Torr) [24].…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggest that past strong exposure activates the PFC during olfactory stimulation in patients with MCS, and strong OFC activation persists after stimulus exposure [17]. Thus, the chemical-sensitive state of patients with MCS might remain due to repeated daily exposure, eventually leading to intolerance to odorous chemicals [17]. …”
Section: Introductionmentioning
confidence: 97%
“…In particular, patients with MCS were demonstrated to peculiarly react to sensory stimuli, with activation of brain areas connected with motivational and emotional processing of the information. We also demonstrated activation in the prefrontal cortex (PFC) during olfactory stimulation [16] and in the orbitofrontal cortex (OFC) [17] following olfactory stimulation in patients with MCS using several different odorants using near-infrared spectroscopy (NIRS) imaging. These results suggest that prefrontal information processing associated with odor-processing neuronal circuits and memory and cognition processes from past hazardous chemical exposure play significant roles in the pathology of MCS [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations